Comparison of Automatically Tuned Cascade Control Systems of Servo-Drives for Numerically Controlled Machine Tools - Mandra, S. (Elektronika ir Elektrotechnika, 2014)
Servo-drives have a significant influence on the tracking accuracy of numerically controlled machine tools. It is important to properly choose the structure and gains of a servo-drive control system. This paper presents a tuning method for position and velocity controllers of digital servo-drives. The proposed method allows the controllers’ gain values regardless of controller types (P, PI, PD or PID) to be determined. It takes into account a number of parameters relevant to practical applications, such as the shape of the position error signal and the resolution of the transducer used to measure the angular position of the motor shaft. The controller gains are determined for a parabolic position command signal. A comparison of the influence of both controllers’ types and feed-forward control types on tracking error is also presented. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.2788